Movimientos e interrogantes en la construcción del territorio de la práctica profesional docente (Praxis Educativa, 2026)
This text presents a systematization of the development of the course “Práctica Profesional” in the University Teacher Education Program in Educational Sciences at the Faculty of Humanities of the UNMdP. It addresses conceptual, didactic, and methodological movements that have shaped its implementation from a situated, critical, and reflective perspective. The purpose of the paper is to offer an articulated reading of the experiences developed, acknowledging their contributions to the education of future teachers of Educational Sciences and identifying ongoing challenges. The text highlights the criteria for selecting partner institutions, the didactic devices implemented, and the promotion of contextualized, collaborative, and critical intervention practices. It proposes the development of methodological tools for the documentation and analysis of practices, leading to projections aimed at strengthening inter-institutionality, deepening interdisciplinary work, and promoting training dispositifs. It offers a framework for thinking about teaching practice in “other” territories from a contextualized, creative, and collectively constructed perspective.